Middle-Income Trap and the Baltic States: Common Challenges, Different Strategies* - Kalanta, Marius (Politologija, 2023)
The paper contributes to further advancing research on the middle-income trap in the Baltic States. It argues, first, that while the Baltic States have already surpassed income levels associated with the middle-income trap and continue converging with advanced economies, they still might face risks of the middle-income trap defined as a difficulty to move into higher value-added positions of the value chain. Second, the paper demonstrates that over the course of recent transformations, growth models of the Baltic States have become increasingly divergent with differences between Estonia and Lithuania being most pronounced. Third, it is argued, that growth model differences also imply different risks associated with the middle-income trap. Estonia faces a risk that its leapfrogging into specialisation of ICT-based services remains premature and incapable to deliver productivity levels comparable to those of advanced economies. Yet, Lithuania faces a risk of being incapable to upgrade its large manufacturing sector. Instead, it risks continuously sustaining labour-intensive export-led growth and further taking advantage of cost-competitiveness by diversifying into new industries while still performing lower value-added activities in them.